Good Corporate Governance dan Kinerja BUMN dengan Penghindaran Pajak sebagai Pemoderasi - Handy Deo Setiadi; Supatmi Supatmi (Postgraduate Program Merdeka University, 2022)
Privatization is one of the Government's efforts to obtain additional capital with one of This study aims to analyze the impact of GCG on company performance with tax avoidance as a moderation variable. The GCG indicators in this research are independent board of commissioners, institutional ownership, audit quality, and proportion of the number of audit committeeswhile company performance is proxied by return on assets. The sample in this research was 13 state-owned companies listed on the Indonesia Stock Exchange for 2016 to 2020. This research used cross-section weights methods for the hypothesis testing. The results of this research show that the audit quality and the proportion of the audit committee have a positive effect on the company's performance,while independent commissioners and institutional ownership have no effect on company performance. This study also finds that tax avoidance is proven only as a moderator by strengthening the positive influence of GCG as measured by institutional ownership on company performance.https://doi.org/10.26905/afr.v4i2.6689